2020
DOI: 10.3390/nu12103096
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Vitis labrusca Leaves Extract on Cardiovascular Dysfunction through HMGB1-TLR4-NFκB Signaling in Spontaneously Hypertensive Rats

Abstract: The Vitis labrusca is a grapevine that has antioxidant, neuroprotective, hepatoprotective, and anticarcinogenic activity. However, the effect of Vitis labrusca leaves on the cardiovascular system is yet to be ascertained. The present study was designed to investigate the effects of Vitis labrusca leaves extract (HP1) on cardiovascular remodeling in spontaneously hypertensive rats. Experiments were performed in rats and were randomly divided into the following groups: Wistar Kyoto rat (WKY), normal control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Very recently, we characterized the phenolic constituents, antioxidant, antibacterial, and, mainly, the antiherpetic activity of grape cane extracts derived from typical cultivars of Southern Italy [11], i.e., Greco, Aglianico, and Fiano. We prepared various extracts in a range of different pHs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), demonstrating that the extraction at pH 13.00 was the optimal condition, since the phenolic yield was the highest. We described the presence of 75 compounds with different abundance profiles at various pHs and, interestingly, six of them were identified for the first time in grape canes.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Very recently, we characterized the phenolic constituents, antioxidant, antibacterial, and, mainly, the antiherpetic activity of grape cane extracts derived from typical cultivars of Southern Italy [11], i.e., Greco, Aglianico, and Fiano. We prepared various extracts in a range of different pHs (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), demonstrating that the extraction at pH 13.00 was the optimal condition, since the phenolic yield was the highest. We described the presence of 75 compounds with different abundance profiles at various pHs and, interestingly, six of them were identified for the first time in grape canes.…”
Section: Introductionmentioning
confidence: 94%
“…Grapevine is a plant rich in bioactive compounds [ 5 , 6 ], known for its therapeutic effects. The grape extract was studied for a long time for its hepatoprotective [ 7 ], hypoglycemic [ 8 ], cardio-protective [ 9 ], antioxidant [ 10 , 11 ], antibacterial [ 11 , 12 , 13 ], and antiviral activity [ 11 , 14 ] which are due to the high levels of polyphenolic compounds found in grapes skin, seeds, and stem. The anti-cancer effect, that has long been studied over the years, is attributable to the consistent antioxidant activity of these molecules [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Special Issue (SI) "Dietary Bioactives: Their Role in the Prevention and Treatment of Cardiovascular and Metabolic Bone Diseases" has published nine novel papers on this topic [7][8][9][10][11][12][13][14][15]. In detail, the SI includes: one narrative review paper, one crosssectional analysis, three pre-clinical animal studies, three in vitro experimental approaches and one ex vivo approach.…”
mentioning
confidence: 99%
“…Using an animal model of ovariectomized-induced osteoporotic mice, the authors identified scopolin as the candidate bioactive compound extracted from Lycii radicis cortex capable of preventing and treating osteoporosis [13]. Finally, in the bone health field, the In this context, the Special Issue (SI) "Dietary Bioactives: Their Role in the Prevention and Treatment of Cardiovascular and Metabolic Bone Diseases" has published nine novel papers on this topic [7][8][9][10][11][12][13][14][15]. In detail, the SI includes: one narrative review paper, one crosssectional analysis, three pre-clinical animal studies, three in vitro experimental approaches and one ex vivo approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation